ONLINE ASSESSMENT DRIVE LEARNING MODEL FOR COMPUTER-BASED TEST PREPARATION OF MEDICAL STUDENTS - Elda Nazriati; Zulharman Zulharman; Firdaus Firdaus (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Computer Based Test (CBT) preparation is important to face the final national exam. During the covid-19 pandemic, it is necessary to modify these preparations online. Assessment can strengthen the learning process, and improve student performance in learning. The purpose of this study was to determine the increase in the ability to do CBT in participants and whether the online drive learning assessment model was well received.Methods: An analytical study was carried out using mixed methods. The research sample were the participants of the Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) preparation for May and August 2021 at FK Unri who met the inclusion criteria, totalling 37 people. Data were collected through questionnaires, FGDs, and secondary data. Hypotheses were tested using Friedman rank test, continued with Wilcoxon signed rank testResults: There was a significant difference between the four integration tests carried out ( firedman test p < 0.001 and Wilcoxon test p <0.005 ), where the highest score was on the 4th integration test. The results showed that 68% of participants were in the satisfied category and 25% of participants were in the very satisfied category. Some of the themes obtained were organization, methods, benefits, learning load, and comparison with similar programs outside campus.Conclusion: The online assessment drive learning model has been proven to improve the ability of participants to take the CBT test for the preparation of UKMPPD. Participants' satisfaction was quite good both quantitatively and qualitatively.